Modern weapons and military equipment for issue 1-2023 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2023)
This Is Russia’s Electronic Warfare Helicopter Jamming In Ukraine; Our First Look At What Fully Upgraded B-52 Bombers Will Look Like; US Army’s XM1299 prototype zero.